Influence Of Physical Activity Level On The Quality Of Life Among Staff Of Adeyemi College Of Education, Ondo - Surajudeen Tosho Bakinde; Sunday Tosin Akinkuade (STKIP Rokania Pasir Pangaraian, 2022)
This study investigated the influence of physical activity level on the quality of life among academic staff of Adeyemi College of Education, Ondo. Expo-facto research design was used in the study. All staff of Adeyemi College of Education, Ondo formed the population. Purposive sampling technique was used to select 39 respondents for the study. The adapted International Physical Activity Questionnaire (IPAQ) and the adapted World Health Organization Health Related Quality of Life (WHO-HRQoL) Questionnaire were used to obtain information from the respondents. Data were analysed using frequency, percentage, mean, standard deviation and independent sample t-test. The results of the findings showed that there is significant difference, t(37) = -3.638, p < .05, between the quality of life of physically inactive academic staff (M = 58.50 ± 2.51) and physically active academic staff (M = 77.03 ± 10.04) of Adeyemi College of Education, Ondo and the t-test value t(37) = -4.112, p < .0001; was obtained for psychological wellbeing. Based on the findings of the study, it was concluded that physically active academic staff have better quality of life and psychological health than the physically inactive academic staff of Adeyemi College of Education, Ondo. It was recommended that there should be adequate sensitization of the staff about the importance of engaging in physical activities during conferences, seminar, health talk and so on . by the physical and health educators and the school management should organize periodic health enhancing physical activity programmes for the staff like fitness walk or jogging once in a month.